Clinical impact of compound sarcopenia in hospitalized older adult patients with heart failure. Issue 7 (18th March 2021) - Attaway, Amy; Bellar, Annette; Dieye, Faty; Wajda, Douglas; Welch, Nicole; Dasarathy, Srinivasan
Abstract: Objectives: Skeletal muscle loss or sarcopenia is a frequent complication in heart failure (HF) and contributes to adverse clinical outcomes. We evaluated if age (primary) and chronic disease (secondary) related sarcopenia, that we refer to as compound sarcopenia, impacts clinical outcomes in hospitalized patients with HF. Design: Cross‐sectional study using hospitalized patient data. Setting: Data from the Agency for Healthcare Research and Quality through the Healthcare Cost and Utilization Project (HCUP). Participants: Hospitalized adult patients with a primary or secondary diagnosis of HF ( n = 64, 476) and a concurrent random 2% sample of general medical population (GMP; n = 322, 217) stratified by age (<50 years of age [y], 51‐65y, >65y) from the Nationwide Inpatient Sample (NIS) database (years 2010–2014). Measurements: In‐hospital mortality, length of stay (LoS), cost of hospitalization per admission (CoH), comorbidities and discharge disposition, with and without muscle loss phenotype, were analyzed. Muscle loss phenotype was defined using a comprehensive code set from international classification of diseases‐9 (ICD‐9). Results: Muscle loss phenotype was observed in 8673 (13.5%) patients with HF compared to 5213 (1.6%) GMP across all age strata. In patients with HF, muscle loss phenotype was associated with higher mortality, LoS, and CoH. Patients with HF (>65y) and muscle loss phenotype had higher mortality (adjusted OR: 1.81; 95% CI 1.56–2.10), CoH (adjusted OR 1.48; 95% CI 1.44–1.1.52), and LoS (adjusted OR 1.40; 95% CI 1.37–1.43) compared to >65y GMP with muscle loss phenotype. Conclusion: Muscle loss phenotype is more commonly associated with increasing age in hospitalized patients with HF. Clinical outcomes were significantly worse in patients with HF aged >65y compared to younger patients with HF and all age strata in GMP with and without a muscle loss phenotype. Abstract : See related editorial by Reeves et al . in this issue.